2021
DOI: 10.1177/15266028211057091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aggressive Wire Recanalization in Calcified Atheroma and Dilatation (ARCADIA) Technique in Eccentric Calcified Lesion of No-stenting Zone

Abstract: Purpose: The endovascular approach for eccentric calcified lesions of the no-stenting zone is challenging. This study aimed to investigate the effect of a novel technique for these lesions. Methods: We performed EVT for severe and eccentric calcified lesions using the technique, which is presented previously and named aggressive wire recanalization in calcified atheroma and dilatation (ARCADIA). In brief, a guidewire is passed to the residual lumen firstly. Next, another guidewire is advanced into and cross th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…First, we performed lesion recanalization by using a guide wire directed into the center of an eccentric calcified plaque. By performing this, we have had utilized an innovative, practical and useful technique in penetrating calcified lesions known as the ARCADIA which was described by Yokota et al 4 The technique demonstrated that it is safe and appropriate for treatment of eccentric calcified lesions of “no‐stenting zone.” 5 This allows the wire to pass through the calcified plaques even in eccentrically located ones. In this way, the burr and cutter of the JETSTREAM Ⓡ device ablates the calcifications in a more central and focused manner, thereby reducing plaque volume effectively with safety in mind.…”
Section: Discussionmentioning
confidence: 99%
“…First, we performed lesion recanalization by using a guide wire directed into the center of an eccentric calcified plaque. By performing this, we have had utilized an innovative, practical and useful technique in penetrating calcified lesions known as the ARCADIA which was described by Yokota et al 4 The technique demonstrated that it is safe and appropriate for treatment of eccentric calcified lesions of “no‐stenting zone.” 5 This allows the wire to pass through the calcified plaques even in eccentrically located ones. In this way, the burr and cutter of the JETSTREAM Ⓡ device ablates the calcifications in a more central and focused manner, thereby reducing plaque volume effectively with safety in mind.…”
Section: Discussionmentioning
confidence: 99%